Synthesis and photoinitiated thiol–ene reactions of exo-mannals – a new route to C-β-d-mannosyl derivatives. Issue 57 (22nd September 2020) - József, János; Debreczeni, Nóra; Eszenyi, Dániel; Borbás, Anikó; Juhász, László; Somsák, László
Abstract : A synthetic procedure was elaborated for O -peracylated exo-mannals. Thiol-ene additions to pyranoid and furanoid exo-mannals gave mannosylmethyl sulfide type adducts with exclusive regio- and β(d )-stereoselectivities including disaccharide mimetics. Abstract : Syntheses of acyl protected exo -mannal derivatives were developed starting from O -peracylated mannopyranoses via the corresponding anhydro-aldose tosylhydrazones under modified Bamford–Stevens conditions. The synthesis of analogous O -peralkylated (benzylated and isopropylenated) derivatives was carried out from pyranoid and furanoid mannonolactones using methylene transfer reagents. Photoinitiated thiol–ene additions of these exo -mannals resulted in the corresponding C -(mannopyranosyl/mannofuranosyl)methyl sulfides in medium to good yields with exclusive regio- and β(d ) stereoselectivities.